Lek attendance of male sage grouse in North Park, Colorado - Emmons, Steven R., author; Ryder, Ronald A., advisor; Braun, C. E., committee member; Hein, Dale, committee member; Lehner, Philip N., committee member (Colorado State University. Libraries, 1980)
Daily lek attendance patterns, breeding season movements, and habitat selection of male sage grouse (Centrocercus urophasianus) were investigated in North Park, Colorado from late March through mid-June 1978-79. Thirty-seven males (20 adults and 17 juveniles) were equipped with radio transmitters and studied on 5 leks. Peak male attendance occurred 25-37 days after peak female attendance on the 3 largest leks investigated. Lek attendance of radio-marked juveniles increased to 91-95% in mid-May and decreased thereafter. Adult male attendance increased to 98-100% in mid-May and then decreased. A non-lek attending segment of the male population was not observed. Juvenile males visited 2-4 leks, remaining on each for an average of 4.3 days. One juvenile visited 2 leks (4.5 km apart) in 1 morning. Most adult males (72.7%) visited only 1 lek but 2 visited 1-2 additional leks for 1 day and 1 moved to an alternate lek after 15 May. Juveniles and adults moved at least 23.9 and 10.0 km, respectively, during the breeding season. Four juvenile males moved from the study area, including a move of over 25 km in 5 days. Three adults moved to leks 12-21 km from the study area. Off-lek locations were within 0.5 and 1.0 km of a lek for 39.9 and 62.6% of 160 locations, respectively. Males typically dispersed over 1 km in non-random directions from leks to feeding and loafing sites. Subsequent mid-day moves over 150-300 m resulted from disturbance. Over 60% of the juveniles (60.4) and adults (69.8) returned to leks in the evening to roost. Sagebrush (Artemisia spp.) canopy coverage and height at 160 feeding-loafing sites averaged 28.1% and 43.5 cm, respectively. Approximately 90% (89.7) of the roosting locations occurred in sagebrush with a canopy coverage of less than 20% (avg. 8.7) and height less than 40 cm (avg. 18.7). Recommended procedures for counting leks are given.
Covers not scanned.
Item deaccessioned after digitization.
Keywords: Sage grouse; Wildlife conservation -- Colorado -- North Park; Wildlife conservation; Colorado -- North Park